In Vitro Membrane Stabilizing and Thrombolytic Activities of Ophirrhiza mungos, Mussaenda macrophylla, Gmelina philippensis and Synedrella nodiflora Growing in Bangladesh - Islam, Farhana; Chowdhury, Sharmin Reza; Sharmin, Tasnuva; Uddin, Md. Gias; Kaisar, Mohammad A.; Rashid, Mohammad A. (Journal of Pharmacy and Nutrition Sciences, 2013)
The methanol extracts and their pet-ether, carbon tetrachloride, chloroform and aqueous soluble partitionates of Ophirrhiza mungos, Mussaenda macrophylla, Gmelina philippensis and Synedrella nodiflorawere subjected to assays for membrane stabilizing and thrombolytic activities. The extractives inhibited heat- as well as hypotonic solution-induced haemolysis of human erythrocytes in vitro. The pet-ether soluble fraction of O. mungos, M. macrophylla and S. nodiflora demonstrated 61.16 % & 24.75%, 52.55% & 23.35% and 60.24% & 22.85% inhibition of hemolysis of RBC caused by hypotonic solution and heat, whereas the carbon tetrachloride soluble fraction of G. philippensis showed 49.05% and 21.25% inhibition of hypotonic and heat induced hemolysis of RBC, respectively. Here, acetyl salicylic acid was used as reference standard at 0.10 mg/mL. Among the four plants, the carbon tetrachloride soluble fraction of O. mungos, methanol extract of M. macrophylla, carbon tetrachloride soluble fraction of G. philippensis and chloroform soluble fraction of S. nodiflora revealed highest thrombolytic activity with clot lysis value of 50.09%, 49.50%, 47.14% and 46.37%, respectively. Standard streptokinase and water were used as positive and negative controls which showed 65.00% and 3.84% lysis of clot, respectively.